Investigating the Impact of Gamification on Student Motivation, Engagement, and Performance - Iván Miguel García-López; Elizabeth Acosta-Gonzaga; Elena Fabiola Ruiz-Ledesma (MDPI AG, 2023)
In the academic context, the use of innovative learning techniques that can have a positive impact in the classroom is becoming increasingly common; gamification is one such technique. This study compared the effects of gamification on engagement, cognition, metacognition, and academic performance when university students used a gamified platform to when they did not in a mathematics course. Using the statistical technique of structural equation modelling (SEM) for both cases, the results show that motivation was the construct with the largest effects, influencing behavioral dissatisfaction, cognition, and metacognition. When students used the gamified platform, motivation influenced behavioral dissatisfaction, which in turn influenced academic performance. On the other hand, when the gamified platform was not used, motivation had a negative effect on academic performance. Therefore, the use of gamification learning strategies can help to reduce student demotivation.